(untitled) (Dimensión Empresarial, 2020)
The objective of this research is responding to two important questions that have been analyzed in the literature on international management, the “where” and the “how”. With this purpose both descriptive and comparison of means analysis are applied. The resulting analysis indicates that Spanish multinationals in the service sector have a semi global focus in their international operations and are located principally in Europe and Latin America. Furthermore, we found that Spanish service multinationals exert high levels of subsidiary control and that do not present significant differences in the levels of control they have over subsidiaries in relation to the type of service.